1985
DOI: 10.1177/002221948501800407
|View full text |Cite
|
Sign up to set email alerts
|

Main and Interaction Effects of Metallic Pollutants on Cognitive Functioning

Abstract: The present study investigated possible relationships of metal levels and metal combinations with children's cognitive functioning. Hair-metal concentrations of lead, arsenic, mercury, cadmium, and aluminum were determined in 69 randomly selected elementary age children. They were also administered the Wide Range Achievement Test reading and spelling tests and the Bender Visual-Motor Gestalt Test. Parents of subjects were interviewed to control for confounding variables that may affect cognitive development. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In a cohort study, the concentration of cadmium was inversely related to IQ (Thatcher et al 1982). Other investigators reported associations between cadmium and children’s performance on verbal IQ and visual-motor and cognitive tasks (ATSDR 1999; Marlowe et al 1985b; Moon et al 1985). However, these studies have received little attention, and it is not clear whether the effects described were due to exposure to cadmium or to other substances (i.e., lead exposure).…”
mentioning
confidence: 99%
“…In a cohort study, the concentration of cadmium was inversely related to IQ (Thatcher et al 1982). Other investigators reported associations between cadmium and children’s performance on verbal IQ and visual-motor and cognitive tasks (ATSDR 1999; Marlowe et al 1985b; Moon et al 1985). However, these studies have received little attention, and it is not clear whether the effects described were due to exposure to cadmium or to other substances (i.e., lead exposure).…”
mentioning
confidence: 99%
“…According to the ATSDR's interaction profiles (ATSDR, , ), the interaction of iAs–Cd–Pb–MeHg for neurological effects may be greater than additive; this observation is mainly based on two findings in children concerning (i) a potentiating interaction of Pb on As‐associated decreases in reading and spelling (Moon, Marlowe, Stellern, & Errera, ) and (ii) the potentiating effects of As or Cd alone on Pb‐induced maladaptive classroom behavior (Marlowe et al., ). Regarding the mechanism of toxicity, both As and Pb react with the sulfhydryl groups of proteins and alter mitochondrial functions, whereas both Cd and Pb inhibit calcium entry into neurons (ATSDR, ).…”
Section: Discussionmentioning
confidence: 99%
“…These data support other recent studies that have correlated increased hair metal levels with mental retardation (Marlowe, Folio, Hall, & Errera, 1982;Marlowe, Errera, & Jacobs, 1983). Studies of general school populations have also linked increasing hair metal levels and their interactions to decrements in psychometric intelligence (Thatcher, Lester, McAlaster, & Horst, 1982;Moon, Marlowe, & Errera, in press), adaptive behavior (Marlowe, Cossairt, Moon, & Errera, 1985), and academic achievement (Moon, Marlowe, Stellern, & Errera, 1985).…”
Section: Discussionmentioning
confidence: 99%